THE EFFECT OF FERTILIZER UREA AND KCL ON ULTISOL AND INCEPTISOL TOWARD SOIL CHEMICAL PROPERTIES ON CORN ( ZEA MAYS L. ) GROWTH - Wira Okriadi Lubis (Universitas Sembilanbelas November Kolaka, 2016)
The research was conducted at green house of Agriculture Faculty, North Sumatera University. The research was done to study on the Urea and KCl fertilizer of chemical effect characteristic and growth of corn plant at Ultisols and Inceptisols. The research designed by randomized block factorial with two factors and four dosage replications. The first factors were kind of soils (Ultisols and Inceptisols). The second factor was Urea and KCl fertilizer, each others at 0 ppm, 100 ppm, 200 ppm, 300 ppm N and 0 ppm, 100 ppm, 200 ppm, 300 ppm K2O. The result showed that application of Urea and KCl fertilizers increased height and dry weight of corn plants, soil acidity, nitrogen content and exchangeable Kalium at Inceptisols. Dosage excess of Urea was more at 100 ppm N responsible on height and weight of corn plant.